Translesion DNA Polymerases and Cancer - Makridakis, Nick; Reichardt, Juergen (Frontiers in Genetics, 2012)
DNA repair has been regarded as an important barrier to carcinogenesis. The newly discovered field of translesion synthesis (TLS) has made it apparent that mammalian cells need distinct polymerases to efficiently and accurately bypass DNA lesions. Perturbation of TLS polymerase activity by mutation, loss of expression, etc. is expected to result in the accumulation of mutations in cells exposed to specific carcinogens. Furthermore, several TLS polymerases can modulate cellular sensitivity to chemotherapeutic agents. TLS genes and TLS gene variations may thus be attractive pharmacologic and/ or pharmacogenetic targets. We review herein current data with regards to the potential contribution of the primary TLS polymerase genes to cancer, their interaction with pharmacologic agents, and identify areas of interest for further research.